2009
DOI: 10.1073/pnas.0805806106
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte cyclooxygenase-2 influences cardiac rhythm and function

Abstract: Nonsteroidal anti-inflammatory drugs selective for inhibition of COX-2 increase heart failure and elevate blood pressure. The COX-2 gene was floxed and crossed into merCremer mice under the ␣-myosin heavy-chain promoter. Tamoxifen induced selective deletion of COX-2 in cardiomyocytes depressed cardiac output, and resulted in weight loss, diminished exercise tolerance, and enhanced susceptibility to induced arrhythmogenesis. The cardiac dysfunction subsequent to pressure overload recovered progressively in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 67 publications
(67 reference statements)
5
107
0
Order By: Relevance
“…51 The finding that coxibs and traditional NSAIDs caused a similar increased risk of heart failure indirectly suggests that the high-dose regimens of these agents used in the coxib trials produced comparable levels of vascular COX-2 inhibition.…”
Section: Effects On Congestive Heart Failurementioning
confidence: 91%
“…51 The finding that coxibs and traditional NSAIDs caused a similar increased risk of heart failure indirectly suggests that the high-dose regimens of these agents used in the coxib trials produced comparable levels of vascular COX-2 inhibition.…”
Section: Effects On Congestive Heart Failurementioning
confidence: 91%
“…Observational studies consistent with a cardiovascular risk have been reported for several traditional NSAIDs, which also exhibit selectivity for inhibition of COX-2, such as diclofenac and meloxicam (2)(3)(4)(5). The clinically manifest elements of this hazard (a predisposition to thrombotic events, an elevation of blood pressure, cardiac failure, and arrhythmogenesis) have been recapitulated in rodent models in which the COX-2-dependent formation of prostacyclin (PGI 2 ) or its action is disrupted (6)(7)(8). This mechanism would be expected to be influenced by the underlying cardiovascular risk of an individual patient (9).…”
mentioning
confidence: 87%
“…Thus, these results provide a novel mechanism through which alterations in mitochondrial bioenergetic state can be used to modulate blood flow and hence substrate delivery. Moreover, hydroxyeicosatetraenoic acids and epoxyeicosatrienoic acids have profound effects on cardiovascular hemodynamic function and ion channel kinetics (75,76).…”
Section: Discussionmentioning
confidence: 99%